The Beginnings of Higher Theatre Education in Spain. First proposals and experiences - Vieites García, Manuel Francisco; Solveira Díaz, Ricardo (Historia y Memoria de la Educación, 2018)
Coinciding with the presentation of reports on the need for a national system of education, from the second half of the 18th century until the first years of the 19th century, several initiatives were formulated in Spain for the creation of a favourable opinion regarding the training of theatre professionals. The creation of theatre schools and the organization of theatres themselves was also encouraged, in general accordance with reports and records. In addition to legitimizing the theatre professions, it also served to bolster the public image of the theatre professionals, as theatre was considered an instrument in popular education. With this paper, written after a review of available literature and an analysis of what configures the scientific and normative cultures in theatre education, we offer a panoramic view of how the idea of an educational justification for professional theatre training was formulated, while also considering some empirical realizations.